Serum Metabolomic Profiling of All-Cause Mortality: A Prospective Analysis in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) Study Cohort. Issue 8 (30th January 2018) - Huang, Jiaqi; Weinstein, Stephanie J; Moore, Steven C; Derkach, Andriy; Hua, Xing; Liao, Linda M; Gu, Fangyi; Mondul, Alison M; Sampson, Joshua N; Albanes, Demetrius
Abstract: Tobacco use, hypertension, hyperglycemia, overweight, and inactivity are leading causes of overall and cardiovascular disease (CVD) mortality worldwide, yet the relevant metabolic alterations responsible are largely unknown. We conducted a serum metabolomic analysis of 620 men in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study (1985–2013). During 28 years of follow-up, there were 435 deaths (197 CVD and 107 cancer). The analysis included 406 known metabolites measured with ultra-high-performance liquid chromatography/mass spectrometry–gas chromatography/mass spectrometry. We used Cox regression to estimate mortality hazard ratios for a 1-standard-deviation difference in metabolite signals. The strongest associations with overall mortality were N -acetylvaline (hazard ratio (HR) = 1.28; P < 4.1 × 10 −5, below Bonferroni statistical threshold) and dimethylglycine, 7-methylguanine, C -glycosyltryptophan, taurocholate, and N -acetyltryptophan (1.23 ≤ HR ≤ 1.32; 5 × 10 −5 ≤ P ≤ 1 × 10 −4 ). C -Glycosyltryptophan, 7-methylguanine, and 4-androsten-3β, 17β-diol disulfate were statistically significantly associated with CVD mortality (1.49 ≤ HR ≤ 1.62, P < 4.1 × 10 −5 ). No metabolite was associated with cancer mortality, at a false discovery rate of <0.1. Individuals with a 1-standard-deviation higher metabolite risk score had increased all-cause and CVD mortality in the test set (HR = 1.4, P = 0.05; HR = 1.8, P = 0.003, respectively). The several serum metabolites and their composite risk score independently associated with all-cause and CVD mortality may provide potential leads regarding the molecular basis of mortality.